Sustainable organophosphorus-catalysed Staudinger reduction. Issue 19 (5th September 2018) - Lenstra, Danny C.; Lenting, Peter E.; Mecinović, Jasmin
Abstract : A highly efficient and sustainable organophosphorus-catalysed Staudinger reduction for the conversion of azides to amines in excellent yields is reported. Abstract : A highly efficient and sustainable catalytic Staudinger reduction for the conversion of organic azides to amines in excellent yields has been developed. The reaction displays excellent functional group tolerance to functionalities that are otherwise prone to reduction, such as sulfones, esters, amides, ketones, nitriles, alkenes, and benzyl ethers. The green nature of the reaction is exemplified by the use of PMHS, CPME, and a lack of column chromatography.